MODELING OF THE OPTIMAL INSTALLATION OF HORIZONTAL WELLS IN WEAKLY PERMEABLE ANISOTROPIC GAS-BEARING RESERVOIRS - Lubkov, M. V.; Mosiichuk, K. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
In order to increase gas production in anisotropic weakly permeable hard reaching reservoirs on the base of combined finite-element-difference method for the non-stationary anisotropic Leibenzon problem of piezoconductivity we have carried out a numerical simulation of the distribution of pressure drop around a horizontal production well in an anisotropic weakly permeable gas-bearing reservoir. We have established that the efficiency of gas recovery around a horizontal production well and, accordingly, its productivity significantly depends on the location of the well in a weakly permeable anisotropic gas-bearing reservoir. Based on the obtained results, for effective exploitation of the anisotropic weakly permeable gas reservoirs, it is necessary to place horizontal production wells in areas with relatively low shear anisotropy of the reservoir’s permeability. If it possible, artificially to increase the parameters of permeability around the production well and gas infiltration on the boundaries of the considered reservoir’s area, it will contribute to increasing of the gas yield and prolonging the productivity of the well during reservoir’s exploitation. At the placing of horizontal wells in anisotropic gas reservoirs, the most effective installation is that would ensure all around supply of the gas phase. This is, on the one hand, there was no blocking of gas from the side of reduced permeability, and on another hand, there was no rapid depletion of the reservoir from the side of increased permeability, and it was ensured a free access of gas to the well from all possible directions. We have shown that the location of the horizontal well in the diagonal direction to the main axes of anisotropy is universal relatively different directions of gas flow, therefore, such location is productive and effective as one.